Identidade latino-americana na obra para violoncelo de José Bragato - Medina, Leonardo (2020)
Qualitative research about José Bragato (1915-2017), an important character of the Argentinian new tango, together with Astor Piazzolla, focusing on his pieces for cello and piano, inspired in tango and others rhythms for Argentina and places he transited in Latin America. His legacy of instrumental music lies in the Space in-Between (SANTIAGO, 2000; HANCIAU, 2004) where coexists the dichotomies of the cultures written/oral, popular/erudite, traditional/modern, local/global. The main objective is to analyze how the compositor engenders the intersection of these dichotomies, in the light of musical topics theory (PIEDADE 2011, 2013) and by the identity and ideological position of the Latin American composer (BÉHAGUE 1992, 2006). Thus, after situating the life trajectory of the protagonist of the research through documental support and field research, the study looks forward to clarify the relationship between the musical materials, on five pieces for cello, and also the sociocultural context of formation and experience of the composer. This could add to the reflection about the importance of the local identity elements not only in the interpreter formation but also of the Latin American citizen.